Legislatively Excluded, Medically Uninsured and Structurally Violated: The Social Organization of HIV Healthcare for African, Caribbean and Black Immigrants with Precarious Immigration Status in Toronto, Canada. (April 2022) - Odhiambo, Apondi J.; Forman, Lisa; Nelson, LaRon E.; O'Campo, Patricia; Grace, Daniel
African, Caribbean and Black immigrants face persistent legislative barriers to accessing healthcare services in Canada. This Institutional Ethnography examines how structural violence and exclusionary legislative frameworks restrict the right to HIV healthcare access for many Black immigrants. We conducted semi-structured interviews with Black immigrants living with HIV ( n = 20) and healthcare workers in Toronto, Canada ( n = 15), and analyzed relevant policy texts. Findings revealed that exclusionary immigration and healthcare legislation shaping and regulating immigrants' right to health restricted access to public resources, including health insurance and HIV healthcare and related services, subjecting Black immigrants with precarious status to structural violence. Healthcare providers and administrative staff worked as healthcare gatekeepers. These barriers undermine public health efforts of advancing health equity and ending HIV "while leaving no one behind." We urge continued policy reforms in Canada's immigration and healthcare systems regarding HIV care access for Canada's precarious status immigrants.